Work-related musculoskeletal disorders among dental surgeons: A pilot study - Abdul Rahim Shaik; B H Sripathi Rao; Akhter Husain; Juliana D'sa (Wolters Kluwer Medknow Publications, 2011)
Aim: To describe the work-related musculoskeletal disorders among on-job dental surgeons. Objectives: To identify the musculoskeletal disorders in terms of perception of pain and stiffness experienced by the dental surgeons due to the rigors of dental work, to determine the prevailing working environment with particular reference to dental work station in relation to musculoskeletal disorders, and to find the association between pain and stiffness experienced by the dental surgeons and the selected socio-demographic variables. Materials and Methods: The study was conducted on 30 graduated dental surgeons having a work experience of 1 year or more, post graduates and faculty members of various specialties at Yenepoya Dental College Hospital, Mangalore. The subjects were selected randomly from the hospital and they were given closed-ended questionnaire to find out perception of pain and stiffness experienced in the past 6 months. The observation of the working environment was done by walk-through observational survey. Results: The study showed that 6.6% dental surgeons always experienced shoulder pain, while 83.3% dental surgeons sometimes experienced back pain and 70% sometimes experienced neck pain. Majority of the dental surgeons (73.3%) experienced stiffness in the back and 23.3% experienced severe pain in their neck. It was observed that the number of patients attended per day by the dental surgeons had a significant association (P = 0.024) with the pain they experienced in their hip/thigh region. The frequency of pain experienced by the dental surgeons in the hip/thigh and knee joints also showed a significant association (P = 0.037) with the height of the dental surgeons. Conclusion: The study revealed that various socio-demographic variables contributed to the musculoskeletal disorders experienced by the dental surgeons. However, the number of patients attended per day by the dental surgeons vis-à-vis pain experienced in the back, wrist, and hip/thigh was significant.